Action needed for the EU Common Agricultural Policy to address sustainability challenges. Issue 2 (8th March 2020) - Pe'er, Guy; Bonn, Aletta; Bruelheide, Helge; Dieker, Petra; Eisenhauer, Nico; Feindt, Peter H.; Hagedorn, Gregor; Hansjürgens, Bernd; Herzon, Irina; Lomba, Ângela; Marquard, Elisabeth; Moreira, Francisco; et al.
Abstract: Making agriculture sustainable is a global challenge. In the European Union (EU), the Common Agricultural Policy (CAP) is failing with respect to biodiversity, climate, soil, land degradation as well as socio‐economic challenges. The European Commission's proposal for a CAP post‐2020 provides a scope for enhanced sustainability. However, it also allows Member States to choose low‐ambition implementation pathways. It therefore remains essential to address citizens' demands for sustainable agriculture and rectify systemic weaknesses in the CAP, using the full breadth of available scientific evidence and knowledge. Concerned about current attempts to dilute the environmental ambition of the future CAP, and the lack of concrete proposals for improving the CAP in the draft of the European Green Deal, we call on the European Parliament, Council and Commission to adopt 10 urgent action points for delivering sustainable food production, biodiversity conservation and climate mitigation. Knowledge is available to help moving towards evidence‐based, sustainable European agriculture that can benefit people, nature and their joint futures. The statements made in this article have the broad support of the scientific community, as expressed by above 3, 600 signatories to the preprint version of this manuscript. The list can be found here (https://doi.org/10.5281/zenodo.3685632 ). A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article.